Gene Mapping, Discovery, and Expression Methods and Protocols - Bina, Minou; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2006)
Completion of the sequence of the human genome and the development of high-throughput technologies have opened a new era of research in biology and medicine. In Gene Mapping, Discovery, and Expression: Methods and Protocols, a panel of researchers from around the world and from a variety of disciplines offer a unique blend of computational tools and experimental techniques for gene mapping, comparative genomics, and studies of the control of gene expression. On the computational side, for beginners in the field, the book describes web-based technologies to localize and map genes, to access and retrieve data from microarray databases, to conduct comparative genomics, and to discover the potential "codes" in genomic DNA that may control the expression of protein-coding genes. Detailed experimental techniques described include methods for studying chromatin structure and allele-specific gene expression, methods for high-throughput analysis and characterization of transcription factor binding elements, and methods for isolation and identification of proteins that interact with DNA. The protocols in the book follow the successful Methods in Molecular Biology$1!" (Bseries format, offering step-by-step instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding pitfalls. Cutting-edge and interdisciplinary, Gene Mapping, Discovery, and Expression: Methods and Protocols offers a collection of DNA-sequence-based technologies for gene discovery, retrieval of gene expression data, discovery of regulatory elements, and discovery of transcription factors that interact with DNA.s
Use of Genome Browsers to Locate Your Favorite Genes -- Methods for Identifying and Mapping Recent Segmental and Gene Duplications in Eukaryotic Genomes -- Identification and Mapping of Paralogous Genes on a Known Genomic DNA Sequence -- Quantitative DNA Fiber Mapping in Genome Research and Construction of Physical Maps -- PRINS for Mapping Single-Copy Genes -- VISTA Family of Computational Tools for Comparative Analysis of DNA Sequences and Whole Genomes -- Computational Prediction of cis-Regulatory Modules from Multispecies Alignments Using Galaxy, Table Browser, and GALA -- Comparative Promoter Analysis in Vertebrate Genomes With the CORG Workbench -- cis-Regulatory Region Analysis Using BEARR -- A Database of 9-Mers from Promoter Regions of Human Protein-Coding Genes -- A Program Toolkit for the Analysis of Regulatory Regions of Genes -- Analysis of Allele-Specific Gene Expression -- Construction of microRNA-Containing Vectors for Expression in Mammalian Cells -- Mining Microarray Data at NCBI$1 (Bs Gene Expression Omnibus (GEO)* -- The Stanford Microarray Database -- Detecting Nucleosome Ladders on Unique DNA Sequences in Mouse Liver Nuclei -- DNA Methyltransferase Probing of DNA-Protein Interactions -- Protein Binding Microarrays (PBMs) for Rapid, High-Throughput Characterization of the Sequence Specificities of DNA Binding Proteins -- Quantitative Profiling of Protein-DNA Binding on Microarrays -- Analysis of Protein-DNA Binding by Streptavidin-Agarose Pulldown -- Isolation and Mass Spectrometry of Specific DNProteins -- Isolation of Transcription Factor Complexes by In Vivo Biotinylation Tagging and Direct Binding to Streptavidin Beads.s
Keywords: Life sciences; Biochemistry; Cell biology; Life Sciences; Biochemistry, general; Cell Biology; Electronic books